2–40 GHz dual‐band dual‐polarised nested Vivaldi antenna. Issue 2 (8th January 2019) - Chen, Dong; Wang, Kun; Zhu, Weihua; Wang, Liquan; Liu, Zhigang; Wang, Tailei; Gao, Jianjun; Zhu, Shouzheng
Abstract : A dual‐band dual‐polarised nested Vivaldi antenna (DBDPVA) is proposed in this study. The antenna consists of two orthogonal dual‐band nested antenna elements. The dual‐band nested antenna element is achieved by nesting a 2–8 GHz double‐slot section outside of an 8–40 GHz double‐slot section on a common substrate. The dual‐band nested antenna element is designed through parametric studies. To realise dual‐polarised radiation, the feeding networks of the horizontal element are lengthened, and two complementary slots are cut in the substrate of horizontal element and a vertical element to arrange them in orthogonal crossed form. The measured −10 dB impedance bandwidths ( S 11) of the 2–8 GHz section and 8–40 GHz sections are ∼2–8 GHz and 8–40 GHz. The antenna elements have similar radiation characteristics after the crossed form arrangement. The measured maximum gain is higher than 4.6 dBi at 2–40 GHz and around 10 dBi at 6–35 GHz. The DBDPVA can be used in radio‐frequency simulation system to expand the bandwidth and polarisation diversity of the system.